High toxocara seroprevalence in patients with rheumatoid arthritis and osteoarthritis - Kaplan, M; Kamanli, A; Kalkan, A; Gulkesen, A; Kuk, S; Ardicoglu, O; Demirdag, K (B M J Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL